Temperature dependence of the radiative recombination time in ZnO nanorods under an external magnetic field of 6 T. - Lee, W; Kiba, T; Murayama, A; Sartel, C; Sallet, V; Kim, I; Taylor, R; Jho, Y; Kyhm, K (Optical Society of American (OSA), 2014)
The Temperature dependence of the exciton radiative decay time in ZnO nanorods has been investigated, which is associated with the density of states for the intra-relaxation of thermally excited excitons. The photoluminescence decay time was calibrated by using the photoluminescence intensity in order to obtain the radiative decay time. In the absence of an external magnetic field, we have confirmed that the radiative decay time increased with temperature in a similar manner to that seen in bulk material (∼ T1.5). Under an external magnetic field of 6 T parallel to the c-axis, we found that the power coefficient of the radiative decay time with temperature decreased (∼ T1.3) when compared to that in the absence of a magnetic field. This result can be attributed to an enhancement of the effective mass perpendicular to the magnetic field and a redshift of the center-of-mass exciton as a consequence of perturbation effects in the weak-field regime.